ANALISIS ISI CERAMAH BUYA YAHYA â€œKETIKA UJIAN HIDUP TERASA MELELAHKANâ€ PADA CHANNEL YOUTUBE AL-BAHJAH TV - Maghfiroh, Lailatul; Masruroh, Sayidah Afyatul (Universitas Hasyim Asy'ari, 2023)
Buya Yahya in a short time has received a lot of attention from the public in an effort to spread Islamic da'wah on YouTube social media through the Al-Bahjah TV channel. This is due to the way Buya Yahya speaks in his lectures which always sound and look interesting, the use of language that is easy to understand, his lectures which are not only consumed by the Indonesian public but also abroad. This research focuses on, the message of Buya Yahya's lecture